Role of long non-coding RNA in chemoradiotherapy resistance of nasopharyngeal carcinoma - Yang, Yang; Yuan, QuPing; Tang, Weijian; Ma, Ya; Duan, JingYan; Yang, GuoNing; Fang, Yuan (Frontiers in Oncology, 2024)
Nasopharyngeal carcinoma (NPC) is a malignant tumor originating from the nasopharyngeal epithelial cells. Common treatment methods for NPC include radiotherapy, chemotherapy, and surgical intervention. Despite these approaches, the prognosis for NPC remains poor due to treatment resistance and recurrence. Hence, there is a crucial need for more comprehensive research into the mechanisms underlying treatment resistance in NPC. Long non coding RNAs (LncRNAs) are elongated RNA molecules that do not encode proteins. They paly significant roles in various biological processes within tumors, such as chemotherapy resistance, radiation resistance, and tumor recurrence. Recent studies have increasingly unveiled the mechanisms through which LncRNAs contribute to treatment resistance in NPC. Consequently, LncRNAs hold promise as potential biomarkers and therapeutic targets for diagnosing NPC. This review provides an overview of the role of LncRNAs in NPC treatment resistance and explores their potential as therapeutic targets for managing NPC.